Post-marketing safety surveillance of sacituzumab govitecan: an observational, pharmacovigilance study leveraging FAERS database - Liu, Wensheng; Du, Qiong; Guo, Zihan; Ye, Xuan; Liu, Jiyong (Frontiers in Pharmacology, 2023)
Sacituzumab govitecan (SG), the first antibody-drug conjugate targeting human trophoblast cell-surface antigen 2 (Trop-2), has been approved by the Food and Drug Administration (FDA) for the treatment of advanced or metastatic breast cancer and urothelial cancer. However, there is currently a dearth of information regarding the safety profiles of SG in a large sample cohort. The objective of the present study is to investigate SG-related adverse events (AEs) in real-world settings leveraging the FDA Adverse Event Reporting System (FAERS) database to guide the safety management of clinical medication. The FAERS database was retrospectively queried to extract reports associated with SG from April 2020 to March 2023. To identify and evaluate potential AEs in patients receiving SG, various disproportionality analyses such as reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS) were employed. Overall, 2069 reports of SG as the “primary suspect” were identified. Noteworthy, SG was significantly associated with an increased risk of blood lymphatic system disorders (ROR, 7.18; 95% CI, 6.58-7.84) and hepatobiliary disorders (ROR, 2.68; 95% CI, 2.17-3.30) at the System Organ Class (SOC) level. Meanwhile, 61 significant disproportionality preferred terms (PTs) simultaneously complied with all four algorithms were adopted. Therein, anemia, thrombocytopenia, neutropenia, leukopenia, diarrhea, asthenia, alopecia, and electrolyte imbalance were consistent with the common AEs described in the clinical trials and specification of SG. Furthermore, unexpected significant AEs include colitis (ROR, 12.09; 95% CI, 9.1-16.08), heart rate increased (ROR, 5.11; 95% CI, 3.84-6.79), sepsis (ROR, 4.77; 95% CI, 3.59-6.34), cholestasis (ROR, 6.28; 95% CI, 3.48-11.36), blood bilirubin increased (ROR, 4.65; 95% CI, 2.42-8.94) and meningitis (ROR, 7.23; 95% CI, 2.71-19.29) were also be detected. The median time to onset of SG-related AEs was 14 (interquartile range [IQR], 7-52) days, with the majority occurring within the initial month of SG treatment. Our study validates the commonly known AEs and also found some potentially emerging safety issues related to SG in real-world clinical practice, which could provide valuable vigilance evidence for clinicians and pharmacists to manage the safety issues of SG.